Comparative study of the effects on the microbiota and leukocyturia of fresh and canned Naftussya water - Popovych, Andriy; Ruzhylo, Sofiya; Zakalyak, Nataliya; Popovych, Dariya; Żukow, Xawery (Quality in Sport, 2022)
Background. Balneotherapy has its rightful place in the arsenal of means of treatment of chronic. The universally recognized gold standard of balneofactors is Naftussya bioactive water. The issue of the loss of its healing properties by Naftussya water after extraction from the subsoil, the possibility of its preservation and transportation remain debatable and relevant. The purpose of this study is to compare the impact of fresh and canned water on the microbiota of feces and urine in patients with chronic pyelonephritis. Materials and Methods. The object of clinical-physiological observation were residents of the city of Truskavets’ (21 men aged 24-67 years and 8 women 33-76 years) with chronic pyelonephritis in remission. The subject of the study were the leukocyturia and bacteriuria levels and components of microbiota of feces. Results. Weekly use of fresh Naftussya water causes an increase in the reduced content of probiotics in the microbiota and a decrease in the increased content of conditionally pathogenic microflora, which is accompanied by a reduction of bacteriuria and leveling of leukocyturia. The beneficial effect on the listed parameters of canned Naftussya water is less pronounced, but the differences are statistically insignificant. Conclusion. The obtained results provide grounds for continuing research into the effects of canned Naftusya water on the body of urological patients.